Complications of percutaneous native kidney biopsies in adults in low and middle-income countries: A Systematic review and meta-analysis - Kajawo, Shepherd (Department of Medicine, 2021)
Introduction: Kidney biopsy supports diagnoses, choice of treatment and prognostication in management of kidney diseases. Complications associated with this procedure varies among countries depending on several clinical and technical factors. This Systematic review and meta-analysis aims to report on these complications in low and middle-income countries (LMIC) and compare the burden of complications across different regions. Methods: Two independent reviewers searched studies from 1st January 1980 to 31st December 2017 in PubMed, Cochrane Reviews and African Journals Online. The study-specific estimates were pooled through a random-effects model meta-analysis to obtain an overall summary estimate of major complications across studies. Statistical heterogeneity was evaluated by the Cochrane's Q statistic. Results: 35 studies reporting on 18,456 kidney biopsies met the inclusion criteria. The overall rate of kidney biopsy complications was 14.0% (95% CI 10.0-18.0%).Major complications occurred in 1.3% (95% CI 0.8 – 2.4%) whilst minor complications were 10.9% (95% CI 0.07.4-14.9%). LMIC in Europe and Central Asia had the highest complications 21.4% (95% CI 19.1 – 23.8%) while East Asia and the Pacific had the least rates 7.9% (95% CI 1.8 – 17.7%); p< 0.001. Blind procedures had the highest overall complications, 21.2% (95% CI 17.6 – 25.0%), followed by pre-marking using ultrasound [13.9% (95% CI 7.8-21.3%) and least complications with real-time ultrasound (p=0.003). Death occurring post kidney biopsy was reported in 2 patients. Conclusion: Major complications associated with kidney biopsies in LMIC were low. However, minor complications still occur in significant proportions. Ultrasound-guided kidney biopsies and appropriate training will mitigate some of these risks.